2019
DOI: 10.3892/mmr.2019.10267
|View full text |Cite
|
Sign up to set email alerts
|

Crocin protects against dexamethasone‑induced osteoblast apoptosis by inhibiting the ROS/Ca2+‑mediated mitochondrial pathway

Abstract: Osteoblast apoptosis has been identified as an important event in the development of glucocorticoid (GC)-induced osteoporosis and osteonecrosis of the femoral head. Crocin, a bioactive ingredient of saffron, has been demonstrated to induce antiapoptotic effects on numerous types of cell in vitro ; however, the effects of crocin on the dexamethasone (Dex)-induced apoptosis of osteoblasts remain unclear. In the present study, the protective effects of crocin during Dex-induced apoptosis of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 44 publications
2
18
0
Order By: Relevance
“…# p < 0.05 vs. control group, *p < 0.05 vs. LPS group participate in hemodynamics [5][6][7][8]25]. As shown in previous reports, crocin had an important protective effects in several diseases by affecting on cell apoptosis, arteriosclerosis, oxidation, and inflammation [15][16][17][18][19]. The present study demonstrated that pretreatment with crocin effectively improved the pulmonary edema associated with albumin leakage by maintaining the integrity of glycocalyx in LPS-induced ARDS mice.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…# p < 0.05 vs. control group, *p < 0.05 vs. LPS group participate in hemodynamics [5][6][7][8]25]. As shown in previous reports, crocin had an important protective effects in several diseases by affecting on cell apoptosis, arteriosclerosis, oxidation, and inflammation [15][16][17][18][19]. The present study demonstrated that pretreatment with crocin effectively improved the pulmonary edema associated with albumin leakage by maintaining the integrity of glycocalyx in LPS-induced ARDS mice.…”
Section: Discussionsupporting
confidence: 76%
“…Crocin is an ester glycoside extracted from saffron. As one of the main active constituents of saffron, crocin has many pharmacological effects, such as anti-oxidation [15], anti-arteriosclerosis [16], anti-apoptosis [17], and anti-inflammatory [18]. However, no studies have reported the effects of crocin on endothelial glycocalyx, HMGB-1, NF-κB, and MAPK signaling pathways in LPS-induced ARDS mice and LPS-stimulated HUVECs.…”
Section: Introductionmentioning
confidence: 99%
“…A previous study has demonstrated that osteoporosis and osteonecrosis are closely related to ONFH. 35 Especially, the inhibition of SMURF1 could improve the bone morphogenetic protein (BMP) signalling and the osteogenic differentiation while enhancing the capacity of bone formation in spinal fusion rats, and meanwhile SMURF1 could elevate the capacity of the bone fracture healing. 36,37 The knockdown of SMURF1 could promote the osteogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…The levels of Mda, a product of the destruction of polyunsaturated fatty acids in the cell membrane, indirectly reflects the grade of oxidative damage. Sod acts as an important antioxidant enzyme by antagonizing and blocking oxygen free radicals to decrease cell damage and thus speeding the repair of free radical-induced damage in cells (54,55). High levels of oxygen free radicals exceed the capacity of the antioxidant system during smoke inhalation injury, which causes lipid peroxidation and subsequent destruction of cell membranes (56).…”
Section: Discussionmentioning
confidence: 99%